2022
DOI: 10.48550/arxiv.2209.08108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anomalous hydrodynamics with triangular point group in 2 + 1 dimensions

Abstract: We present a theory of hydrodynamics for a vector U(1) charge in 2+1 dimensions, whose rotational symmetry is broken to the point group of an equilateral triangle. We show that it is possible for this U(1) to have a chiral anomaly. The hydrodynamic consequence of this anomaly is the introduction of a ballistic contribution to the dispersion relation for the hydrodynamic modes. We simulate classical Markov chains and find compelling numerical evidence for the anomalous hydrodynamic universality class. Generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As an aside, we further note that if K β€² ΜΈ = 0, then consistency with the second law of thermodynamics then requires that K ΜΈ = 0 in (3.21) [34]. More recently, it was shown that the existence of such a K β€² term will require an exotic kind of chiral anomaly [42], which can be found in actual lattice models (but is unlikely to exist in electron fluids).…”
Section: Continuity Equations and Constitutive Relationsmentioning
confidence: 85%
“…As an aside, we further note that if K β€² ΜΈ = 0, then consistency with the second law of thermodynamics then requires that K ΜΈ = 0 in (3.21) [34]. More recently, it was shown that the existence of such a K β€² term will require an exotic kind of chiral anomaly [42], which can be found in actual lattice models (but is unlikely to exist in electron fluids).…”
Section: Continuity Equations and Constitutive Relationsmentioning
confidence: 85%
“…More generally, the first-order derivatives will annihilate all functions spanned by 𝑔(𝑧) = 𝑧 𝑛 and 𝑔(𝑧) = 𝑖𝑧 𝑛 for 𝑛 ∈ N 0 . Such holomorphic conserved charges also arise in the context of hydrodynamics in the presence of a triangular point group when the current tensor transforms in the vector representation of D 3 [52].…”
Section: Vector Conserved Quantitiesmentioning
confidence: 99%
“…If we had not included 𝑓 (x) = 𝑦 3 βˆ’ 3π‘₯ 2 𝑦 in M, we would additionally be able to introduce a second third-order derivative, D 2 = πœ• 3 𝑦 βˆ’ 3πœ• 2 π‘₯ πœ• 𝑦 . We note in passing that the operator D 1 also naturally appears in the context of hydrodynamics in the presence of the point group D 3 , since it may be written compactly as D 1 = πœ† 𝑖 𝑗 π‘˜ πœ• 𝑖 πœ• 𝑗 πœ• π‘˜ , with πœ† 𝑖 𝑗 π‘˜ the third-order D 3 -invariant tensor [52,53].…”
Section: Subsystem Symmetries In 2d From 𝑢 (1) Symmetriesmentioning
confidence: 99%